Pengaruh Teknologi Informasi Berbasis Payment Gateway,Inovasi Dan Orientasi Kewirausahaan Terhadap Kinerja UMKM ( Studi Empiris Pada UMKM Di Kota Pekanbaru) - Sahrawani, Risma Ihza; Marlina, Evi; Fitriana, Nur (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to determine the influence of payment gateway-based information technology, innovation and entrepreneurial orientation on the performance of MSMEs (empirical study on MSMEs in Pekanbaru City). The population in this research is Micro, Small and Medium Enterprises in Pekanbaru City, totaling 7,309 MSMEs in 2022. The sample selection for this research was based on the purposive sampling method. So the sample in the research was 100 MSMEs, especially culinary delights in Pekanbaru City. The type of data used in this research is quantitative data in the form of secondary data with collection techniques using questionnaires. The data analysis technique uses multiple regression and is tested using the t test. The research results show that payment gateway-based information technology, innovation and entrepreneurial orientation have a significant effect on the performance of MSMEs (empirical study on MSMEs in Pekanbaru City).